Risk of Essure microinsert abdominal migration: case report and review of literature. - Ricci, Giuseppe; Restaino, Stefano; Di Lorenzo, Giovanni; Fanfani, Francesco; Scrimin, Federica; Mangino, Francesco P (Ther Clin Risk Manag, 2014)
PURPOSE: To report a case of Essure microinsert abdominal migration and literature review. METHODS: A 41-year-old woman was counseled to undergo Essure sterilization. The procedure was hampered by the presence of endometrial cavity adhesions, obscuring left tubal ostium. By using microscissors the adhesions were progressively lysed. Since the procedure had become very painful, the patient required general anesthesia. Once adhesion lysis was completed, the tubal ostium was well visible. Both devices were then easily introduced into the fallopian tubes. At the end of the procedure, five coils were visible on the right side and five coils on the left side, as recommended. RESULTS: The 3-month hysterosalpingogram follow-up suspected abdominal migration of the left device. Laparoscopy confirmed the device displacement in the left lower abdominal quadrant. Both fallopian tubes and the uterus appeared normal. No signs of perforation were detected. The device was embedded into the omentum, but it was easily removed. Bilateral tubal sterilization was performed by bipolar coagulation. CONCLUSION: There are only 13 cases, including the present, of Essure abdominal migration in the literature. In most cases, abdominal displacement of the microinsert is asymptomatic and does not induce tissue damage. However, in some cases, it may cause a severe adverse event, requiring major surgery. Therefore, removal of the migrated device should be performed as soon as possible. Moreover, during presterilization counseling, the patient should also be correctly informed about the risk of this rare but relevant complication, as well as about the surgical interventions that could be required to solve it.